Analysis of The Poetry "My Love Is Far On The Island" By Chairil Anwar With a Mimetic Approach - Julia Putri Nabil (Bulletin of Social Studies and Community Development, 2022)
Abstract: Poetry is a literary work that emphasizes aesthetics in the use of language and has the meaning contained therein. Poetry is not easy for readers to understand, because the language is wide and the meaning is difficult to interpret. So the reader must have knowledge of poetry studies in order to understand the meaning conveyed. The poem "Cintaku Jauh di Pulau" by Chairil Anwar has simple language, but has a broad meaning. The purpose of this study is to analyze poetry with a mimetic approach. Mimetic is an approach in literary criticism regarding imitation of real life. The method used in this study is a descriptive method that examines the content of the meaning of the poem "Cintaku Jauh di Pulau"   Keywords: poetry, cintaku jauh di pulau, mimetic approach